Review of fungus-feeding urothripine species from China, with descriptions of two new species (Thysanoptera:Phlaeothripidae) - Tong, Xiaoli; Zhao, Chao (Zootaxa, 2017)
Twelve species of urothripine Phlaeothripidae are recorded from China, including two new species that are described and illustrated here, Stephanothrips austrinus sp. n. and Urothrips calvus sp. n. A new key is provided to the urothripine species known from China together with new collection data.